2012
DOI: 10.1002/ijc.27797
|View full text |Cite
|
Sign up to set email alerts
|

Novel prognostic protein markers of resectable pancreatic cancer identified by coupled shotgun and targeted proteomics using formalin‐fixed paraffin‐embedded tissues

Abstract: Pancreatic cancer is among the most lethal malignancies worldwide. We aimed to identify novel prognostic markers by applying mass spectrometry (MS)-based proteomic analysis to formalin-fixed paraffin-embedded (FFPE) tissues. Resectable, node positive pancreatic ductal adenocarcinoma (PDAC) with poor (n 5 4) and better (n 5 4) outcomes, based on survival duration, with essentially the same clinicopathological backgrounds, and noncancerous pancreatic ducts (n 5 5) were analyzed. Cancerous and noncancerous cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…outcome PDAC. These results further confirmed by IHC showing Ech overexpression in the poor outcome group [9]. There were no significant correlations between the expression of Ech and clinicopathological parameters like tumor location, tumor size, lymph node or distant metastasis at the time of resection.…”
Section: Pancreatic Cancersupporting
confidence: 82%
See 1 more Smart Citation
“…outcome PDAC. These results further confirmed by IHC showing Ech overexpression in the poor outcome group [9]. There were no significant correlations between the expression of Ech and clinicopathological parameters like tumor location, tumor size, lymph node or distant metastasis at the time of resection.…”
Section: Pancreatic Cancersupporting
confidence: 82%
“…Majority of exocrine pancreatic cancers are pancreatic ductal adenocarcinoma (PDAC). Studies of pancreatic cancer using serum/plasma and tissue samples are few [8,9].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…It has been previously reported that pancreatic cancer with higher OLFM4 gene expression has increased malignant behavior and invasive capacity as well as the ability to metastasize more easily (30). OLFM4 expression is upregulated in early colorectal and gastric cancer but downregulated in progressive or advanced tumors (2,31).…”
Section: Discussionmentioning
confidence: 98%
“…Takadate et al identified Nm23/nucleoside diphosphate kinase-A as a dFdC-sensitivity marker by means of comprehensive proteome analysis in dissected pancreatic cancer tissues. 17 However, other molecules included in Fig. 1 were not found in that study.…”
Section: Introductionmentioning
confidence: 89%